Prevalence of stress among medical students and music to alleviate the stress - Zareena, Shifa (International Journal of Research in Medical Sciences, 2017)
Background: Stress has become a cup of coffee in everybody's life. Adults to some extent are able to cope with it. But the young chaps are put into more stressful situations by the society. They find it difficult to handle it at a very early age and end up being a victim of various addictions. The aim of the study was to survey the prevalence of stress among the medical students and their choice of preference to alleviate from stress. Methods: The study was a cross sectional study of random sampling method with a sample size of 100 medical students belonging to age group 18-21 years. Informed consent was obtained from each individual. The study was cleared by the ethics committee. The stress level of each participant was assessed using the student stress scale questionnaire. Results: Of the 100 students who completed the questionnaire, 38% of the students belonged to the ‘no stress’ category, 51% fell under ‘mild stress’ category, 8% under ‘moderate stress’ and 3% under ‘severe stress’ category. Of the 62 students who showed certain degree of stress levels, 47 (76%) students prefer music as a choice for relief from stress and 15 (24%) prefer other modes of relief such sleeping or talking to a friend, etc. Conclusions: Medical students are prone to a lot of stress during their course of study and music is the preferred choice for most students to relieve them from stress.